Inkjet-printed low-dimensional materials-based complementary electronic circuits on paper - Irene Brunetti (Nature Portfolio, 2021)
Abstract Complementary electronics has represented the corner stone of the digital era, and silicon technology has enabled this accomplishment. At the dawn of the flexible and wearable electronics age, the seek for new materials enabling the integration of complementary metal-oxide semiconductor (CMOS) technology on flexible substrates, finds in low-dimensional materials (either 1D or 2D) extraordinary candidates. Here, we show that the main building blocks for digital electronics can be obtained by exploiting 2D materials like molybdenum disulfide, hexagonal boron nitride and 1D materials such as carbon nanotubes through the inkjet-printing technique. In particular, we show that the proposed approach enables the fabrication of logic gates and a basic sequential network on a flexible substrate such as paper, with a performance already comparable with mainstream organic technology.